Sustainable electrical insulator waste management: an eco-friendly concrete development and property assessment using 3E analysis - R., Ranjith; S. K., Sekar (Frontiers in Sustainability, 2025)
A green environment will result from the use of sustainable industrial waste in eco-friendly concrete making. This study summarizes the outcomes of mechanical properties, microstructure characterization, and Environmental–Energy–Economic (3E) analysis of four different M50 grade structural concrete using industry-dumped-out ceramic electrical insulator waste as a substitute for conventional cement and granite aggregates. The optimum quantity of insulator powder in concrete making is found to be 30%. The concrete with 30% insulator powder and 100% insulator aggregates (M4 mix) performs better by achieving significantly higher mechanical properties such as compressive strength, split tensile strength, flexural strength, dynamic and static modulus at 9.29%, 17.50%, 14.42%, 8.31%, and 11.65%, respectively, compared to reference concrete (M1 mix; with 100% cement and 100% granite aggregates). Regression and statistical analysis predictions of R2 > 98% and coefficient of Variation (CV) >5% had a substantial influence on the mechanical properties of insulator concrete. The hydration mechanism of insulator concrete mix M4 increases the chemically bound water (Wb) to 3.24% as found by thermo-gravimetric analysis. Similarly, a 2.20% higher Si-O-Si bond wavenumber enhances the concrete strength as evaluated by Fourier Transform Infrared (FTIR) analysis. Based on the eco-friendly analysis, the maximum specific energy consumption, CO2 emission reduction, and Sustainability Index (SI) were achieved by the M4 mix at 33.58%, 31.28%, and 3.15% respectively. In light of these findings, insulator waste can be used as a cement and aggregate substitute in concrete with 36% of economic benefit.